Is thrombolysis beneficial in elderly patients with minor ischemic stroke? - Naess, Halvor (Frontiers in Stroke, 2024)
Introduction A pooled analysis of data from randomized controlled trials showed that thrombolysis is an effective treatment in patients older than 80 years of age with acute ischemic stroke. However, the outcomes in daily clinical practice may differ from those observed in randomized controlled trials. Thus, the present study aimed to compare the short-term outcomes of patients older than 80 years of age with ischemic stroke or transient ischemic attacks (TIA) admitted to Haukeland University Hospital in Norway, examining thrombolysis vs. non-thrombolysis treatment in patients. Methods All patients with acute ischemic stroke or TIA who were older than 80 years of age and admitted to Haukeland University Hospital within the 4.5-h window after stroke onset between 2006 and 2020 were prospectively included in this observational study. Patients who received thrombolysis were compared to patients who did not receive thrombolysis. The endpoint was a modified Rankin Scale (mRS) score on day 7 or discharge if earlier. The National Institutes of Health Stroke Scale (NIHSS) scores were recorded repeatedly during their hospital stays. Results In total, 808 patients were included. Thrombolysis was given to 393 (49%) patients. In patients with an NIHSS score of <3 (minor ischemic stroke) at admission, thrombolysis was associated with worse short-term outcomes (β = 0.13, p = 0.03), whereas thrombolysis was associated with better short-term outcomes in patients with an NIHSS score of ≥3 (major ischemic stroke) at admission (β = 0.12, p = 0.003). Thrombolysis appeared to be associated with neurological worsening in patients with an NIHSS score of <3 at admission. Excluding patients who underwent a thrombectomy did not change the results. Conclusion In elderly patients with major ischemic stroke, thrombolysis was associated with better short-term outcomes. However, in patients with minor ischemic stroke, thrombolysis was associated with worse short-term outcomes. Several reasons for this discrepancy are discussed.